(untitled) (Research, Society and Development, 2021)
The genus Mikania (Asteraceae) comprises about 450 species of these, 203 are found in Brazil and present several chemical and biological activities. Considering the variety of species and their therapeutic properties, the present study aimed to perform technological prospecting of this genus, since this approach aims to contribute to technological, scientific and innovation research. For this purpose, the patent documents were analyzed, regarding the applicant countries, year of filing and the international classification of patents of the genus Mikania. The search was conducted in the databases World Intellectual Property Organization (WIPO), European Patent Office (EPO) and the National Institute of Industrial Property (INPI) in October 2020, using the descriptor “Mikania”; present in the title and/or abstract in addition, documents that included medicinal approaches were selected. Thus, taking into consideration the filing countries, Japan, Brazil and the United States led the patent deposits, with the first document filed in 1991 and the largest number of applications in the years 2000 and 2010. The data concerning the international patent classification are concentrated in subclass A61K, which deals with preparations for medical, dental or hygienic purposes. These results demonstrated the therapeutic and technological potential of the Mikania species and thus which can be evidenced the potential of this study.